2023
DOI: 10.3390/s23083866
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of International Affective Picture System (IAPS) around the World

Abstract: Standardized Emotion Elicitation Databases (SEEDs) allow studying emotions in laboratory settings by replicating real-life emotions in a controlled environment. The International Affective Pictures System (IAPS), containing 1182 coloured images as stimuli, is arguably the most popular SEED. Since its introduction, multiple countries and cultures have validated this SEED, making its adoption on the study of emotion a worldwide success. For this review, 69 studies were included. Results focus on the discussion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 147 publications
1
3
0
Order By: Relevance
“…In threatening contexts, previous studies have associated a similar cardiac deceleration to a post-encounter phase, when threat is present but not imminent (Rösler & Gamer, 2019;Stegmann et al, 2023) and interpreted it as an autonomic response that facilitates information gathering and action preparation, thus helping individuals avoiding or escaping threatening stimuli (Roelofs & Dayan, 2022;Tseng et al, 2023). Here we demonstrate for the first time that cardiac deceleration was greater and longer lasting in the predictable vs. unpredictable condition, only in threat trials (see also Branco et al, 2023).…”
Section: Discussionsupporting
confidence: 73%
“…In threatening contexts, previous studies have associated a similar cardiac deceleration to a post-encounter phase, when threat is present but not imminent (Rösler & Gamer, 2019;Stegmann et al, 2023) and interpreted it as an autonomic response that facilitates information gathering and action preparation, thus helping individuals avoiding or escaping threatening stimuli (Roelofs & Dayan, 2022;Tseng et al, 2023). Here we demonstrate for the first time that cardiac deceleration was greater and longer lasting in the predictable vs. unpredictable condition, only in threat trials (see also Branco et al, 2023).…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, females generally reported slightly higher arousal and lower valence ratings for the same stimuli. These findings suggest that males might experience positive images as more emotionally stimulating, while females might perceive these images as less pleasant and more intense (Branco et al, 2023;Rosalind et al, 2023). This difference highlights the importance of considering gender when analyzing emotional responses.…”
Section: Hypotheses Regarding Secondary Outcomesmentioning
confidence: 83%
“…Numerous studies have demonstrated psychophysiological changes in response to emotional stimuli, accompanied by behavioral changes in terms of postural responses, vocal reactions and facial expressions (see [6] for review). Emotions confer a priority of control on states of readiness for action, claiming (not always successfully) priority in the control of behavior [5].…”
Section: The Historic Interaction Between Emotion Motivation and Moto...mentioning
confidence: 99%